PROFESSIONAL COMPETENCE REQUIREMENTS: THE VIEWS OF SEVERAL PHYSICAL AND SPORTS EDUCATION TEACHERS (CASE IN MOSTAGANEM PROVINCE, ALGERIA) - A Laroua, M Bensabeur, O Benbernou, J M Sebbane, HM Benkazdali, A Belkadi (http://euinstitute.net/, 2015)
The purpose of this study was to identify the opinions of Physical and Sports Education (PSE) teachers regarding professional competence and the specific requirements of the work. A questionnaire was drawn up and sent to 85 PSE teachers in secondary schools based the Mostaganem “Wilaya” or Province in Algeria. The findings indicate that this group of teachers could not clearly define general or specific competence. However, they largely agreed that the teacher/coach plays a very important role in establishing the professional competence of trainees. Competence that is specific to PSE is described in studies as “how to apply competence by competence the approach to teaching PSE” and “knowing how to apply legislation”. None of the teachers responding cited a basic competence in the professional sphere, described in the literature: sound knowledge of legislation and administrative procedures. In addition, the findings show that the teachers are not satisfied with the training they received and that it does not enable them to reinvest their training in their professional role. From the opinions expressed by the population studied, their training does not encourage professionalism. This finding is also confirmed by research by Laroua et al (2014).
Keywords: Competence, Professional Competence, PSE, Algeria, Mostaganem